O-034 Abciximab Therapy for Thromboembolic Complications of Neuroendovascular Procedures. (29th July 2016) - Kansagra, A; Madaelil, T; Cross, D; Moran, C; Derdeyn, C
Abstract : Background: Thromboembolic complications sustained during neuroendovascular procedures can result in postoperative infarcts if not promptly recognized and treated. Treatment commonly involves glycoprotein IIb/IIIa inhibitors such as abciximab. We aimed to retrospectively review angiographic and clinical outcomes following abciximab administration for thromboembolic complications at our institution. Methods: Neuroendovascular cases with thromboembolic complications treated with abciximab over a 132 month period were identified using a search of a comprehensive, prospectively maintained case log and all angiography records for the terms "abciximab" or "ReoPro." Intraoperative intra-arterial (IA) administration typically involved slow infusion of 10 mg abciximab over 5 to 10 minutes. Intraoperative intravenous (IV) administration 0.25 mg/kg abciximab. Postoperative IV infusion typically involved 10 mcg/min infusion of abciximab. All relevant clinical notes and neuroimaging were reviewed. Results: Of 19, 566 neuroendovascular procedures performed during the review period, 48 (0.25%) involved abciximab administration for thromboembolic complications. 65% (31/48) involved IA administration, 21% (10/48) were IV only, and 15% (7/48) were combined IA and IV. Intraoperative treatment was supplemented with postoperative abciximab infusion in 13% (6/48) patients. Angiographic improvement was seen in 92% (44/48) cases, including 65% (31/48) with complete angiographic resolution (Figure 1 ). Only 8% (4/48) cases failed to improve angiographically. Angiographic outcomes were similar in patients who received IA, IV, or combined IA and IV administration of abciximab intraoperatively ( p = 0.58), or patients who did or did not receive continuous IV infusion of abciximab postoperatively ( p = 0.11). Postoperative infarction was seen in 20% (5/25), 44% (4/9), and 67% (4/6) following IA, IV, and combined IA and IV abxicimab, respectively ( p = 0.06) (Figure 1 ). The rate of postoperative infarction was 33% (2/6) in patients who received continuous IV infusion of abciximab postoperatively and 32% (11/34) in those who did not ( p = 1.00). Postoperative infarction developed in 8% (2/24) patients with complete angiographic improvement, compared to 69% (11/16) in patients with partial or no improvement ( p < 0.0001). Conclusion: Abciximab administration is an effective method of treating thromboembolic complications of neuroendovascular procedures. Angiographic outcomes were not appreciably different between different routes of abciximab administration. Infarction was least common in patients treated with IA abciximab; the addition of postoperative abciximab infusion did not affect the rate of infarction. No or partial angiographic improvement was associated with significantly higher rates of postoperative infarction than complete angiographic improvement. Disclosures: A. Kansagra: None. T. Madaelil: None. D. Cross: None. C. Moran: 2; C; Medtronic Neurovascular. 3; C; Medtronic Neurovascular. C. Derdeyn: None.